1999
DOI: 10.1017/s0007485399000073
|View full text |Cite
|
Sign up to set email alerts
|

Modelling development time of Myzus persicae (Hemiptera: Aphididae) at constant and natural temperatures

Abstract: The development period from birth to adult of alate and apterous virginoparae of the green peach aphid, Myzus persicae (Sulzer), reared on Brassica campestris ssp. chinensis, was measured at 13 constant and five natural temperature regimes. The day-degree model, the logistic equation, and the Wang model were used to describe the relationships between temperature and development rate at constant conditions. The constant temperature-development curves derived from the three models were used with a Weibull functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 41 publications
1
41
0
1
Order By: Relevance
“…Our results showed that the egg stages of A. hygrophila (excluding cold treatment periods) were significantly shorter after exposure to temperatures at 4-12°C for 4 or 7 days, compared with those at constant 25°C. As Liu and Meng (1999) pointed out that development thresholds, produced by the linear regression technique or by nonlinear models, do not model the processes that control development at low temperatures. They are simply notional estimates of thresholds derived by extrapolation from development rates at moderate and high temperatures, and thus are not points with any intrinsic relationship to a true development threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the egg stages of A. hygrophila (excluding cold treatment periods) were significantly shorter after exposure to temperatures at 4-12°C for 4 or 7 days, compared with those at constant 25°C. As Liu and Meng (1999) pointed out that development thresholds, produced by the linear regression technique or by nonlinear models, do not model the processes that control development at low temperatures. They are simply notional estimates of thresholds derived by extrapolation from development rates at moderate and high temperatures, and thus are not points with any intrinsic relationship to a true development threshold.…”
Section: Discussionmentioning
confidence: 99%
“…bT, where a and b are constants. The thermal requirement for development was then estimated as k = 1/b degree-days (Campbell et al 1974;Liu and Meng 1999). The linear model can also be used to estimate the lower developmental threshold by T 0 = -a/b°C, for comparison purposes with the non-linear model.…”
Section: Rearing and Collectionmentioning
confidence: 99%
“…The lower threshold temperature for development (Tlower) was calculated using the following equation (Liu & Meng, 1999):…”
Section: Statisticsmentioning
confidence: 99%
“…where Dt is the developmental time in days at temperature x (°C) and b is the regression coefficient (Arnold, 1959(Arnold, , 1960Madubunyi & Koehler, 1974;Liu & Meng, 1999).…”
Section: Statisticsmentioning
confidence: 99%